(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
This study examined the degree of variations in DNA fingerprints associated with slight altitudinal change of Schinus molle grown in Abha region, Saudi Arabia. Seven populations from Schinus molle plants located at 2193.0, 2246.0, 2197.7, 2441.0, 2372.0, 2250.6 and 2175.0 meters had been investigated. The degree of genetic variability was evaluated using random amplified polymorphic DNA (RAPD), mixed RAPD and intersimple sequence repeat markers (ISSR). The genetic similarity coefficients from RAPD analysis revealed the maximum similarity value (89.9%) was between population at 2250.6 m and population at 2175.0 m. The genetic similarity coefficients from mixed RAPD primers displayed the highest similarity value (87.6%) between population at 2246.0 m and population at 2197.7 m. Similarity coefficients from ISSR analysis revealed the highest similarity value (86.2%) among populations at 2193.0 m, 2246.0 m, 2441.0 m and at 2250.6 m. Super tree analysis (RAPD + mixed RAPD + ISSR) showed the highest similarity value (85.5%) between population at 2441.0 m and population at 2250.6 m. In conclusion, marker systems including RAPD, mixed RAPD and ISSR, alone or combined can be effectively used in determining the genetic relationship among Schinus molle plants even at very close populations. Bangladesh J. Plant Taxon. 24(2): 205–214.